RANCANG BANGUN SISTEM PENGAMAN PADA SEPEDA MOTOR DENGAN MEMANFAATKAN SENSOR ENCODER DAN SENSOR PING - Kurnia Dwi Artika (ROTOR, 2013)
The natural wealth of South Kalimantan is no doubt. abundant from across the border, so many stood mining companies, and housing estates. this resulted in local residents' income increases. Welfare is increased compared to regions or islands. With geographical location filled with hills, forests, plantations and swamps, became an important means of transportation in the mobilization of the results of mining, plantation and trading activities. Therefore, it takes a vehicle in the path of effective special / alternative narrow, winding, uphill and downhill to the extreme. The access road is worth it difficult to pass by the four wheels though. So one solution is a two-wheeled vehicle, the motorcycle. but the problem is security vehicles lately theft rife in both daytime or at night, in the house or outside the house, still theft can be done.Existing security system is not adequate to cope with theft / vehicle crime lately. so that the necessary breakthrough in addressing this problem by installing two sensors at the same time the ping ultrasonic sensor and encoder sensor. with the provisions of the ideal distance and height is obtained from ping ultrasonic sensor 0.4 meters and encoder sensor 4.92 meters. Keywords: ping ultrasonic sensor, encoder, mikrokontroller, lcd